Type of Mental of Successful Entrepreneur: A Qualitative Study of Bob Sadino’s Experience - Masrukhin, Agus (Humaniora, 2015)
This paper was to determine the type of mental of successful businessman Bob Sadino. So he became a major employer in the field of retail and supermarket. The theories used were personality theory and Cash flow Quadrant theory. The theories used were later associated with the analysis results obtained from the field. Research used descriptive qualitative analysis using mental of success. Results show that Bob Sadino had Business owner mental and Investor mental based on Cash flow Quadrant theory.